THE EFFECT OF ACADEMIC AND NON-ACADEMIC SERVICES ON STUDENT SATISFACTION OF AKADEMI PARIWISATA MEDAN HOTEL SCHOOL - Tambunan, Susi Marta (SEAN Institute, 2022)
One of the satisfactions for service users is quality service. The services provided by an educational institution are in the form of academic and non-academic services. Medan Hotel School Tourism Academy always tries to provide the best service to students. This study looked at the influence of academic and non-academic services on student satisfaction as service users. It can be seen that the academic services provided by this institution affect student satisfaction significantly, as well as non-academic services also significantly affect the satisfaction of students of the Medan Hotel School Tourism Academy. Simultaneously, academic and non-academic services also affect student satisfaction. The influence given is quite large, namely as much as 86 percent on student satisfaction as evidenced in the coofesien of determination. This study used a random sample of 45 students from various semesters and used